KEPEMIMPINAN KEPALA DESA DALAM PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT (COMMUNITY BASED TOURISM) DI DESA PONGGOK KECAMATAN POLANHARJO KABUPATEN KLATEN - Ainii, Aziizah Qurrotu; ., Kushandajani (Journal of Politic and Government Studies, 2019)
Ponggok village is one of the villages included in the Disadvantaged Village Inpres, since Ponggok Village was headed by the Village Head Junaedhi Mulyono, SH Ponggok Village tourism in Ponggok Village began to develop and received numerous awards from the regional to the national level. The question that arises: What is the leadership of the Ponggok Village Chief in the development of community-based tourism? The research objective was to determine the leadership of the Ponggok Village Chief in developing community-based tourism.Efforts to answer the problems and objectives of the research are carried out using the theory of leadership traits and also the theory of community-based tourism development. The object of this research is tourism in Ponggok Village.The results of the study showed that in the leadership of Ponggok Village Chief Junaedhi Mulyono, SH community-based tourism development can be seen through four dimensions possessed by leaders based on trait theory namely intelligence dimensions, maturity and freedom of social relations, self motivation and achievement motivation, human relations. Ponggok Village Chief Junaedhi Mulyono, SH has strategies in the form of spatial, sectoral, community resource and information technology approaches. Tourism development in Ponggok Village always involves the community from planning to the evaluation stage and always paying attention to environmental aspects and also the wisdom of the local culture.